School lunch as a break or an educational activity: A quantitative study of Swedish teacher perspectives. Issue 6 (2nd October 2017) - Waling, Maria; Olsson, Cecilia
Abstract : Purpose: The purpose of this paper is twofold: first, to explore to what extent teachers eat together with pupils during school lunches and their attitudes toward using these lunches to reach the educational goals stated in the Swedish compulsory school curriculum; and second, to study to what degree teachers see themselves and school meal personnel as role models during school lunches. Design/methodology/approach: A questionnaire was completed by 3, 629 teachers in Swedish schools. Findings: In total, 90 percent of the teachers ate lunch together with the pupils one or more days per week. The majority reported that meals were fully (54 percent), or partially (40 percent) subsidized when they were eating with pupils. In total, 72 percent thought that school lunches should be considered part of the school's educational activities while 28 percent thought that it should be a time to get a break from educational activities. Most teachers thought that school lunches could be useful for learning about the issues of food waste and healthy eating while there were more diverse views on using lunches for learning about fundamental values. A majority of the teachers considered themselves to be role models in the school meal situation. Practical implications: The authors suggest that the educational component of the school meal per se should be regulated in the Educational Act together with guidelines from the Swedish National Agency for Education. Originality/value: This study is unique since it covers a previously little studied area; teachers' attitudes toward using the school lunch situation for educational purposes.